2020
DOI: 10.1002/zaac.201900280
|View full text |Cite
|
Sign up to set email alerts
|

β‐Diketiminato Rare‐Earth Metal Complexes: The Influence of Monoatomic Substituents in the N‐aryl Moieties on Structures and Properties

Abstract: Treatment of β‐diketiminate ligands bearing different N‐aryl monoatomic substituents [HLH = (C6H5)N = C(Me)CH=C(Me)NH(C6H5), HLF = (2,6‐F2C6H3)N=C(Me)CH=C(Me)NH(2,6‐F2C6H3), and HLCl = (2,6‐Cl2C6H3)N=C(Me)CH=C(Me)NH(2,6‐Cl2C6H3)] with Ln(CH2SiMe3)3(THF)2 (Ln = Y and Lu) afforded a variety of β‐diketiminato rare‐earth metal complexes depending on substituents, namely, phenyl ring C–H bond activated complexes (L')(LH)Lu(THF) (1b, L' = (C6H4)N = C(Me)CH=C(Me)N(C6H5)), six‐coordinate homoleptic complexes (LH)3Ln [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…However, the polymers by asymmetric complexes 60 and 61 were atactic under the same conditions. After adjusting the substituents to chlorine atoms, the resulting complexes 62 and 63 showed a slight decrease in the isoselectivity for 2‐VP polymerization under organoboron salt activation ( mm =94 % or 91 %) (Table 5, Runs 5 and 6) [23] …”
Section: Stereoselective Polymerization Of 2‐vinylpyridinementioning
confidence: 99%
“…However, the polymers by asymmetric complexes 60 and 61 were atactic under the same conditions. After adjusting the substituents to chlorine atoms, the resulting complexes 62 and 63 showed a slight decrease in the isoselectivity for 2‐VP polymerization under organoboron salt activation ( mm =94 % or 91 %) (Table 5, Runs 5 and 6) [23] …”
Section: Stereoselective Polymerization Of 2‐vinylpyridinementioning
confidence: 99%
“…In 2018, Cui and colleagues 8 demonstrated that β-diketiminato yttrium complexes [ L 1 Y(CH 2 SiMe 3 )(THF)] + [ L 1 = (2,6-Et 2 C 6 H 3 )NC(Me)CHC(Me)N(2,6-Et 2 C 6 H 3 )] ( Y-1 ) and [ L 2 Y(CH 2 SiMe 3 )(THF)] + [ L 2 = (2,6-Cl 2 C 6 H 3 )NC(Me)CHC(Me)N(2,6-Cl 2 C 6 H 3 )] ( Y-2 ) were effective in catalyzing the polymerization of 2-vinylpyridine (2VP) to produce isotactic polymers. But their analogue [ L 3 Y(CH 2 SiMe 3 )(THF)] + [ L 3 = (2,6-C 6 H 5 )NC(Me)CHC(Me)N(2,6- i Pr 2 C 6 H 3 )] ( Y-3 ) yielded atactic polymers under identical conditions (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…In the previous work, we have reported the influence of the halogen substituents on the structures of β-diketiminato rare-earth metal complexes. 50 To explore the halogenated β-diketiminate ligands with other metals, herein, we presented a series of halogenated β-diketiminato magnesium complexes and their catalytic performances for the ROP of aliphatic lactones.…”
Section: Introductionmentioning
confidence: 99%
“…We envisioned that the introduction of electron‐withdrawing halogen substituents could increase the Lewis acidity of metal center, facilitate the coordination of monomer, and enhance the catalytic activity. In the previous work, we have reported the influence of the halogen substituents on the structures of β‐diketiminato rare‐earth metal complexes 50 . To explore the halogenated β‐diketiminate ligands with other metals, herein, we presented a series of halogenated β‐diketiminato magnesium complexes and their catalytic performances for the ROP of aliphatic lactones.…”
Section: Introductionmentioning
confidence: 99%